Edukasi Pijat Commond Cold dalam Mengatasi Batuk Pilek pada Balita di Desa Cinennung - Musni Musni; Desi Heriyana (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
: Coughs and colds in babies and toddlers can be caused by many factors. Most of the causes are viruses. Treatment for acute coughs and colds can be done in 2 ways, namely pharmacological and non-pharmacological. Non-pharmacological treatment can be complementary therapy or common cold therapy, which is a relaxation therapy to reduce feelings of anxiety and depression in respiratory tract disorders. The aim of this activity is to increase mothers' knowledge about how to do Common Cold massage for non-pharmacological treatment of coughs and colds. Community service activities are carried out to increase students' knowledge about the impact of early marriage. Community service activities are carried out using the lecture (counseling) method and practicing the Common Cold massage method. Before and after counseling students were given pre-test and post-test questionnaires. As a result of this activity, mothers' knowledge before counseling was in the good category was 5 people (26.3%) and after counseling, knowledge in the good category increased to 17 people (89.5%). This shows that there is an increase in mothers' knowledge about Common Cold massage therapy after the counseling was carried out.